2013
DOI: 10.1371/journal.pone.0067462
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of TaLEA Gene from Tamarix androssowii Improves Salt and Drought Tolerance in Transgenic Poplar (Populus simonii × P. nigra)

Abstract: Late embryogenesis abundant (LEA) genes were confirmed to confer resistance to drought and water deficiency. An LEA gene from Tamarix androssowii (named TaLEA) was transformed into Xiaohei poplar ( Populus simonii × P. nigra) via Agrobacterium . Twenty-five independent transgenic lines were obtained that were resistant to kanamycin, and 11 transgenic lines were randomly selected for further analysis. The polymerase chain reaction (PCR) and ribonucleic acid (RNA) gel blot indicated that the TaLEA gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 27 publications
2
20
0
1
Order By: Relevance
“…It has been reported that ABA regulates the expression of abiotic stress-responsive genes (P5CS, P5CR, TPS, TPP, NHX and LEA) and biotic stress-responsive genes (CAS, POD, HRGP, LTP, LRP1, CPI, PI and AMP) in several plant species (Abraham et al, 2003;Asselbergh et al, 2008;Dalal et al, 2009;Gao et al, 2009Gao et al, , 2013Hildmann et al, 1992;Iturriaga et al, 2009;Jung et al, 2004;Lee and Hwang, 2009;Muñoz-Mayor et al, 2012;Pramanik and Imai, 2005;Schluepmann and Paulb, 2009;Song et al, 2011;Sripinyowanich et al, 2013;Sun et al, 2014;Tseng et al, 2013;Yokoi et al, 2002;Zhu, 2002). The application of ABA has been shown to enhance the resistance to Pythium irregulare in Arabidopsis (Adie et al, 2007), necrosis virus in tobacco (Iriti and Faoro, 2008) and Alternaria solani in tomato (Song et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ABA regulates the expression of abiotic stress-responsive genes (P5CS, P5CR, TPS, TPP, NHX and LEA) and biotic stress-responsive genes (CAS, POD, HRGP, LTP, LRP1, CPI, PI and AMP) in several plant species (Abraham et al, 2003;Asselbergh et al, 2008;Dalal et al, 2009;Gao et al, 2009Gao et al, , 2013Hildmann et al, 1992;Iturriaga et al, 2009;Jung et al, 2004;Lee and Hwang, 2009;Muñoz-Mayor et al, 2012;Pramanik and Imai, 2005;Schluepmann and Paulb, 2009;Song et al, 2011;Sripinyowanich et al, 2013;Sun et al, 2014;Tseng et al, 2013;Yokoi et al, 2002;Zhu, 2002). The application of ABA has been shown to enhance the resistance to Pythium irregulare in Arabidopsis (Adie et al, 2007), necrosis virus in tobacco (Iriti and Faoro, 2008) and Alternaria solani in tomato (Song et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Only in this way, can the mechanisms and principles be discovered and the corresponding solutions are proposed. In addition, there are other factors such as LEA proteins, WRKY and MYB transcriptional factors affecting salt tolerance of plants which should also arouse our attentions (Cheng et al, 2013;Gao et al, 2013;Scarpeci et al, 2013). The microorganisms in the soil is found to be involved in phytohormonal signaling to improve plant nutrition, photosynthesis and biomass production ameliorating crop salt tolerance (Dodd & Pérez-Alfocea, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Glycine-rich SbASR1 contains 63 percent disorder-promoting amino acid residues, and transgenic plants displayed improved adaptation to high-salt stress (De Jonge et al, 2000;Jha et al, 2012). The expression of TsLEA1 from Thellungiella salsuginea and TaLEA from Tamarix androssowii in yeast mutants improved salt tolerance (( Table 2) Zhang et al, 2012;Gao et al, 2013)). Similarly, another nuclear localized Suaeda liaotungensis ASR gene exhibited salt tolerance in transgenic Arabidopsis (Hu et al, 2014).…”
Section: Osmolyte Mediated Salt Tolerancementioning
confidence: 99%